PHYTASE AS A FACTOR IN PHOSPHORUS ABSORPTION - O Kananykhina; T Turpurova (Zernovì Produkti ì Kombìkorma)
The modern world cannot be imagined without the consumption of biotechnology products. One of the key aspects of this development is the provision of high-quality and effective animal feed. Enzymes play a special role in animal nutrition, their industrial production and use takes place in many countries of the world. This is due to the fact that approximately one third of the organic matter contained in feed is not digested by the animal. Reducing these losses by 2-3% allows obtaining additional hundreds of tons of livestock products. It is especially recommended to introduce enzymes into the diet of young farm animals, whose enzymatic digestive system is not yet sufficiently developed. The biosynthesis and activity of digestive enzymes in the animal body undergo significant changes with age, growth rate, and diet composition, which results in different utilization of nutrients. The introduction of enzyme preparations into compound feeds ensures stable digestion conditions and better transformation of feed into livestock products. Today, the cost of mineral supplements is rapidly increasing. To solve the problem of optimizing energy and mineral components, increasing the availability of phosphorus and other mineral elements present in compound feeds, use the enzyme phytase. In grain feeds, a significant part of the phosphorus is chemically bound by phytates. The basis of phytates is inositol, one molecule of which connects six molecules of phosphoric acid via an ester bond. Only phytase is capable of breaking down phytates - an enzyme of plant or microbial origin, the addition of which to the diet of farm animals, including laying hens, improves phosphorus digestibility and balances the calciumphosphorus ratio. The current state of the grain processing industry is analyzed and the feasibility of using grain processing byproducts in poultry feeding is substantiated. Screening showed that phytase increases the bioavailability of nutrients contained in plant-based feeds, and also allows for a significant reduction in the level of inorganic phosphate input. The use of enzymes with different spectrums of action in feeding is an effective mechanism for regulating the mineral nutritional content of the diet by increasing the availability of protein and energy. It also makes it possible to replace expensive feed components with cheaper ones and reduce the cost of livestock products.